Improved Method for Predicting the Performance of the Physical Links in Telecommunications Access Networks - Ferenc Lilik; Szilvia Nagy; László T. Kóczy (Complexity)
A novel approach is presented which is able to predict the available maximal data transfer rate of SHDSL connections from measured frequency dependent electrical parameters of wire pairs. Predictions are made by a fuzzy inference system. The basis of the operable and tested method will be introduced, then an improved version is shown, in which the problems derived from sampling of continuous functions of electrical parameters are eliminated by wavelet transformation. Also possibilities for simplification of the problem and a way of reducing the dimensions of the applied rule bases are presented. As the set of the measured data leads to sparse rule bases, handling of sparseness is unavoidable. Two different ways—fuzzy interpolation and various membership functions—will be introduced. The presented methods were tested by measurements in real telecommunications access networks.